Garberia heterophylla Garberia: FPS-221/FP221, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed description of Garberia heterophylla, a low shrub native to Florida. It highlights the plant’s distinctive features, including its grayish foliage, lavender pink flowers, and obovate leaves. The shrub is noted for its drought tolerance, preference for acidic soils, and ability to attract butterflies. It is suitable for use in reclamation projects, borders, and mass plantings. The document also covers the plant’s growth habits, soil and light requirements, and pest resistance, emphasizing its utility and aesthetic appeal in landscaping. Original publication date October 1999.